Integrated Urban Design Methodology of “Planning-Construction-Management” and Intelligent Management and Control Based on Teaching Reproduction Robot - Haipeng Wang (Journal of Robotics)
With regard to the problems in the integrated urban construction based on “planning-construction–management,” the main issues that include the tight construction cycle, the high operation standards, the relatively extensive range of management data sources, the uneven information control, the relatively significant difficulty of management and control, and so on. In this paper, an integrated urban system of “planning-construction-management” based on the management level of the construction projects is established mainly through the application of the teaching reproduction robot (TRR), the engineering information, management and control procedures, and the system framework and performance. Among them, the management and control cover the design control, the quality supervision, the schedule control module, the safety control, the video monitoring, and the facility movement control. The digital technology is included to achieve an integrated management and control model for the engineering design, construction, and operation in its practical operational form. The introduction of the management and control described above has led to relatively good results for the project by operating on the road project with a public-private partnership (PPP) in the startup area of the Chengdu Tianfu International Airport New Town.